Degradable metal fat-reducing wire as well as preparation method and application thereof
By using a combination of degradable metal wire and absorbable polymer coating in the buried wire weight loss material, the existing buried wire weight loss material has been solved for short maintenance time and rebound, achieving long-term fat loss effect and improving the material's Security and durability.
Patent Information
- Application Number
- CN202411393754.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-07
AI Technical Summary
The existing buried weight loss materials have a short effective maintenance time, are prone to rebound, and have adverse reactions to the human body, making it difficult to achieve long-term fat loss effect.
The degradable metal wire is used and covered with an absorbable polymer coating, and is prepared by hot extrusion, heat drawing and polishing to form a magnesium or zinc alloy metal fat reduction line. The polymer coating controls the degradation rate to extend the fat reduction effect.
It extends the time of fat consumption, avoids rebound and multiple burial lines, produces local alkalinity and calories during the degradation process, promotes fat hydrolysis, and achieves a lasting fat loss effect. The material is safe, non-toxic and has no side effects.
Smart Images

Figure CN119258283A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical devices, and in particular to a degradable metal fat-reducing thread and a preparation method and application thereof. Background Art
[0002] In recent decades, with economic development and improved living standards, overweight / obesity has become a global epidemic that seriously threatens human health. Overweight / obesity can induce a variety of metabolic diseases, such as diabetes, hypertension, ischemic heart disease and cancer. The number of deaths caused by overweight or obesity worldwide is as high as 2.8 million each year, which is the fifth largest risk of death in the world. Obesity is a chronic, recurrent, progressive disease state, and a complex social problem. From a biomedical perspective, obesity can be understood as an excess of energy caused by individual factors such as genetics, diet, lifestyle and behavior, psychological factors and other factors (such as occupation, education, socioeconomics, health literacy, disease status, medication, etc.). At the same time, environmental drivers and more distal system dynamics (such as policy, economic, social, and political factors) largely affect individual behavior, thereby affecting the occurrence of overweight and obesity.
[0003] At present, the prevention and treatment methods of obesity include lifestyle intervention, drug weight loss, surgical weight loss, acupuncture weight loss, etc. Among them, drug weight loss has obvious effect, but the weight loss medicine contains a large amount of laxative ingredients, which may stimulate the endocrine system after taking it, and may even damage the liver and kidneys, thus affecting human health. Surgery for weight loss is often used for some obese patients, and the effect is significant, but the side effects are obvious, and it is easy to rebound. Acupuncture weight loss can consume fat by stimulating the corresponding acupoints, but it also needs to be combined with exercise or diet control, otherwise the effect is mostly not obvious. Thread embedding weight loss is an extension and development of acupuncture weight loss, and is a modified external moxibustion. The medical effect of thread embedding weight loss is based on the principle of traditional Chinese medicine acupuncture. By stimulating the acupoints of the human body, it can play a role in weight loss treatment. At present, the materials for thread embedding weight loss on the market have developed from traditional catgut to polycarboxylic acid glycolic acid PLGA. PLGA is a high molecular polymer with extremely low physical stimulation tissue response. It is treated once every one to two weeks, with little trauma during thread embedding and no adverse reactions. However, the main disadvantages of thread embedding weight loss are that the effective maintenance time is short, it is easy to rebound, and multiple thread embeddings are required. Secondly, these materials have some adverse reactions with the human body. Summary of the invention
[0004] The purpose of the present invention is to provide a degradable metal fat-reducing thread and a preparation method and application thereof. The degradation rate of the degradable metal fat-reducing thread provided by the present invention is controllable, acupoints can be stimulated continuously, the fat consumption time is prolonged, the effective maintenance time is long, and rebound and multiple thread embedding are avoided.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a degradable metal fat-reducing thread, comprising a degradable metal wire and a polymer coating covering the surface of the degradable metal wire;
[0007] The polymer coating is composed of an absorbable polymer.
[0008] Preferably, the material of the degradable metal wire is magnesium, zinc or magnesium-zinc alloy, and the diameter of the degradable metal wire is 0.07-0.3 mm.
[0009] Preferably, the absorbable polymer is at least one of polylactic acid, poly-L-lactic acid PLLA, polylactic acid-glycolic acid copolymer PLGA, polydioxanone PDO, and polydioxanone PPDO.
[0010] Preferably, the polymer coating has a thickness of 2 to 30 μm.
[0011] The present invention also provides a method for preparing the degradable metal fat-reducing thread described in the above technical solution, comprising the following steps:
[0012] (1) hot extruding and hot drawing a degradable metal ingot in sequence to obtain a wire;
[0013] (2) cutting and polishing the wire obtained in step (1) in sequence to obtain a polished wire;
[0014] (3) spraying an absorbable polymer on the surface of the polished wire obtained in step (2) to form a polymer coating to obtain a degradable metal fat-reducing wire.
[0015] Preferably, the extrusion ratio of the hot extrusion in step (1) is (180-500):1, the extrusion temperature of the hot extrusion is 220-500° C., and the diameter of the hot extruded wire is 0.5-3 mm.
[0016] Preferably, the hot drawing in step (1) is a multi-pass drawing, the diameter of the wire material is reduced by 0.1 to 0.2 mm in each drawing pass, and the temperature of the hot drawing is 70 to 120°C.
[0017] Preferably, the length of the wire material after cutting in step (2) is 1 to 4 cm.
[0018] Preferably, the polishing liquid used in step (2) is a mixture of phosphoric acid and ethanol, the polishing time is 15 to 40 seconds, and the polishing temperature is 10 to 35°C.
[0019] The present invention also provides the use of the degradable metal fat-reducing thread described in the above technical solution in the preparation of a thread embedding device.
[0020] The present invention provides a degradable metal fat-reducing thread, the main body of which is a degradable metal wire, and also includes a polymer coating covering the surface of the degradable metal wire. The degradable metal fat-reducing thread provided by the present invention can be inserted into the acupuncture point until the fat layer by acupuncture. After being inserted into the acupuncture point, it plays a role of continuously stimulating the acupuncture point, thereby achieving a fat-reducing effect, and after being implanted in the fat layer, it will continue to degrade to produce local alkalinity and release heat, which can promote the hydrolysis of fat; the polymer coating on the surface can control the degradation rate of the degradable metal wire, prolong the total degradation time of the degradable metal fat-reducing thread, thereby prolonging the time of consuming fat or stimulating acupuncture points, effectively maintaining a long time, and avoiding rebound and multiple thread embedding. In addition, the raw materials of the degradable metal fat-reducing thread provided by the present invention are magnesium, zinc and their alloys, which are widely available, cheap, and have significant economic and social benefits. The polymer coating is an absorbable polymer, which is non-toxic and has no side effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a schematic diagram of the structure of the degradable metal fat-reducing thread provided by the present invention, wherein 1 represents the main body is a degradable metal wire, and 2 represents a polymer coating covering the surface of the degradable metal wire;
[0022] Figure 2 This is a graph showing the percentage of sheep weight within 120 days after the degradable metal fat-reducing threads prepared in Examples 1 and 2 of the present invention and the uncoated degradable metal wire prepared in Comparative Example 1 were implanted into the sheep's tail;
[0023] Figure 3 These are staining images of sheep tail fat tissue sections at 15 days, 30 days, 60 days, 90 days and 120 days after the degradable metal fat-reducing thread prepared in Example 2 of the present invention and the uncoated degradable metal wire prepared in Comparative Example 1 were implanted into the sheep tail;
[0024] Figure 4 This is a graph showing the change in the area of fat cells over time within 120 days after the degradable metal wire prepared in Example 2 of the present invention and the uncoated degradable metal wire prepared in Comparative Example 1 were implanted into the sheep's tail;
[0025] Figure 5 It is a line graph of the weight loss rate of the degradable metal wire prepared in Example 2 of the present invention and the uncoated degradable metal wire prepared in Comparative Example 1 implanted in the sheep's tail within 120 days. DETAILED DESCRIPTION
[0026] The present invention provides a degradable metal fat-reducing thread, comprising a degradable metal wire and a polymer coating covering the surface of the degradable metal wire;
[0027] The polymer coating is composed of an absorbable polymer.
[0028] In the present invention, unless otherwise specified, the raw materials used are conventional commercial products in the art.
[0029] In the present invention, the material of the degradable metal wire is preferably magnesium, zinc or magnesium-zinc alloy; the diameter of the degradable metal wire is preferably 0.07-0.3 mm, more preferably 0.1-0.28 mm. The present invention controls the diameter of the degradable metal wire within the above range to control the full degradation time of the degradable metal fat-reducing thread, prolong the time of consuming fat or stimulating acupoints, avoid rebound and multiple thread embedding, and at the same time reduce the foreign body sensation caused by the degradable metal wire to the human body.
[0030] In the present invention, the absorbable polymer is preferably at least one of polylactic acid, poly-L-lactic acid PLLA, polylactic acid-glycolic acid copolymer PLGA, polydioxanone PDO, and polydioxanone PPDO; the molecular weight of the absorbable polymer is preferably 100,000 to 200,000.
[0031] In the present invention, the thickness of the polymer coating is preferably 2 to 30 μm, more preferably 4 to 25 μm, and further preferably 7 to 20 μm. The present invention controls the thickness of the polymer coating within the above range to control the degradation rate of the degradable metal wire, prolong the total degradation time of the degradable metal fat-reducing thread, thereby prolonging the time of consuming fat or stimulating acupoints, effectively maintaining a long time, avoiding rebound and multiple thread embedding, and at the same time reducing the foreign body sensation caused by the degradable metal wire to the human body.
[0032] The present invention also provides a method for preparing the degradable metal fat-reducing thread described in the above technical solution, comprising the following steps:
[0033] (1) hot extruding and hot drawing a degradable metal ingot in sequence to obtain a wire;
[0034] (2) cutting and polishing the wire obtained in step (1) in sequence to obtain a polished wire;
[0035] (3) spraying an absorbable polymer on the surface of the polished wire obtained in step (2) to form a polymer coating to obtain a degradable metal fat-reducing wire.
[0036] The present invention sequentially performs hot extrusion and hot drawing on a degradable metal ingot to obtain a wire material.
[0037] In the present invention, the material of the degradable metal ingot is preferably magnesium, zinc or magnesium-zinc alloy.
[0038] In the present invention, the extrusion ratio of the hot extrusion is preferably (180-500):1, more preferably (200-400):1; the extrusion temperature of the hot extrusion is 220-500°C, more preferably 250-400°C; the diameter of the hot extruded wire is preferably 0.5-3 mm, more preferably 1-2 mm.
[0039] In the present invention, the hot drawing is preferably multi-pass drawing; the diameter of the wire is preferably reduced by 0.1-0.2 mm in each drawing pass; the temperature of the hot drawing is preferably 70-120°C, more preferably 80-100°C.
[0040] After obtaining the wire material, the present invention cuts and polishes the wire material in sequence to obtain the polished wire material.
[0041] In the present invention, the length of the cut wire is preferably 1 to 4 cm.
[0042] In the present invention, the polishing liquid used for polishing is preferably a mixture of phosphoric acid and ethanol. More preferably, it is a mixture of phosphoric acid and ethanol in a volume ratio of 1:2; the polishing time is preferably 15 to 40 seconds, more preferably 20 to 30 seconds; the polishing temperature is preferably 10 to 35°C. The present invention removes surface oil and oxide layer of the cut wire through polishing, which is beneficial to subsequent spraying.
[0043] After obtaining the polished wire material, the present invention sprays an absorbable polymer on the surface of the polished wire material to form a polymer coating to obtain a degradable metal fat-reducing thread.
[0044] In the present invention, the spraying liquid used for spraying is a solution of an absorbable polymer, and the concentration of the absorbable polymer in the spraying liquid is (0.1-0.5) g / 100 mL; the flow rate of the injection pump used for spraying is preferably 0.6-1.0 mL / min, the spraying speed is preferably 40-80 mm / s, and the number of spraying cycles is preferably 10-40 times.
[0045] After the spraying is completed, the present invention sequentially performs vacuum packaging and irradiation sterilization on the sprayed product to obtain a degradable metal fat-reducing thread.
[0046] In the present invention, the heat-sealing time of the vacuum package is preferably 1 to 4 seconds, and the air extraction time of the vacuum package is preferably 2 to 6 seconds.
[0047] In the present invention, the radiation source used for the irradiation sterilization is preferably Co60, and the time for the irradiation sterilization is preferably 3 to 6 hours.
[0048] The present invention also provides the use of the degradable metal fat-reducing thread described in the above technical solution in the preparation of a thread embedding device.
[0049] In the present invention, the degradable metal fat-reducing thread is preferably implanted into the fat layer or inserted into an acupuncture point until reaching the fat layer.
[0050] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] Example 1
[0052] A degradable metal fat-reducing thread, comprising a degradable metal wire with a length of 2 cm and a diameter of 0.2 mm, and a polymer coating with a thickness of 4 μm covering the surface of the degradable metal wire;
[0053] The polymer coating is composed of absorbable poly-L-lactic acid (PLLA) with a molecular weight of 150,000;
[0054] The preparation method of the above-mentioned degradable metal fat-reducing thread comprises the following steps:
[0055] (1) A pure magnesium ingot is cut into a cylindrical ingot, the cylindrical ingot is kept at 300°C for 3 hours, and then the 20 mm diameter cylindrical ingot is extruded into a hot extruded wire with a diameter of 1 mm at 300°C at an extrusion ratio of 400:1;
[0056] The hot-extruded wire is subjected to multiple passes of hot drawing to obtain a wire with a diameter of 0.2 mm; the diameter of the wire is reduced by 0.1 mm in each drawing pass, and the hot drawing temperature is 80°C.
[0057] (2) physically cutting the wire obtained in step (1) to obtain a cut wire with a length of 2 cm, and then polishing to remove surface oil and oxide layer to obtain a polished wire;
[0058] The polishing liquid used for the polishing is a mixture of phosphoric acid and ethanol in a volume ratio of 1:2. The polishing time is 25 seconds and the polishing temperature is room temperature.
[0059] (3) spraying absorbable PLLA on the surface of the polished wire obtained in step (3) to form a polymer coating with a thickness of 4 μm, and then sterilizing by irradiation after vacuum packaging to obtain a degradable metal fat-reducing thread;
[0060] The spraying liquid used for the spraying is a hexafluoroisopropanol solution of PLLA with a molecular weight of 150,000, the concentration of PLLA in the spraying liquid is 0.25 g / 100 mL, the flow rate of the injection pump used for the spraying is 0.6 mL / min, the spraying speed is 40 mm / s, and the number of spraying cycles is 10 times;
[0061] The heat sealing time of the vacuum package is 2.3 s, and the air extraction time of the vacuum package is 4.0 s.
[0062] The radiation sterilization uses a radiation source Co60, and the radiation sterilization time is 4 hours.
[0063] Example 2
[0064] A degradable metal fat-reducing thread, comprising a degradable metal wire with a length of 2 cm and a diameter of 0.2 mm, and a polymer coating with a thickness of 10 μm covering the surface of the degradable metal wire;
[0065] The polymer coating is composed of absorbable poly-L-lactic acid (PLLA) with a molecular weight of 150,000;
[0066] The degradable metal fat-reducing thread of Example 2 was prepared in the same manner as Example 1, except that the thickness of the polymer coating was 10 μm.
[0067] Example 3
[0068] A degradable metal fat-reducing thread, comprising a degradable metal wire with a length of 2 cm and a diameter of 0.2 mm, and a polymer coating with a thickness of 7 μm covering the surface of the degradable metal wire;
[0069] The polymer coating is composed of absorbable poly-L-lactic acid (PLLA) with a molecular weight of 150,000;
[0070] The degradable metal fat-reducing thread of Example 3 was prepared in the same manner as Example 1, except that the thickness of the polymer coating was 7 μm.
[0071] Example 4
[0072] A degradable metal fat-reducing thread, comprising a degradable metal wire with a length of 2 cm and a diameter of 0.2 mm, and a polymer coating with a thickness of 15 μm covering the surface of the degradable metal wire;
[0073] The polymer coating is composed of absorbable poly-L-lactic acid (PLLA) with a molecular weight of 150,000;
[0074] The degradable metal fat-reducing thread of Example 4 was prepared in the same manner as Example 1, except that the thickness of the polymer coating was 15 μm.
[0075] Example 5
[0076] A degradable metal fat-reducing thread, comprising a degradable metal wire with a length of 2 cm and a diameter of 0.2 mm, and a polymer coating with a thickness of 10 μm covering the surface of the degradable metal wire;
[0077] The polymer coating is composed of absorbable polylactic acid with a molecular weight of 150,000;
[0078] The degradable metal fat-reducing thread of Example 5 was prepared in the same manner as in Example 1, except that the polymer coating was composed of polylactic acid with a thickness of 10 μm and a molecular weight of 150,000.
[0079] Example 6
[0080] A degradable metal fat-reducing thread, comprising a degradable metal wire with a length of 2 cm and a diameter of 0.2 mm, and a polymer coating with a thickness of 10 μm covering the surface of the degradable metal wire;
[0081] The polymer coating is composed of absorbable polydioxanone with a molecular weight of 150,000;
[0082] The degradable metal fat-reducing thread of Example 5 was prepared in the same manner as in Example 1, except that the polymer coating was composed of polydioxanone with a thickness of 10 μm and a molecular weight of 150,000.
[0083] Comparative Example 1
[0084] A coating-free biodegradable metal wire, the specific preparation method of which is as follows: extruding a pure magnesium cylindrical ingot from 20 mm to a wire of 1.0 mm at a temperature of 300°C; continuously hot drawing the extruded wire at 80°C to make the diameter increase from 1.0 to 0.2 mm to obtain a magnesium wire; cutting the obtained magnesium wire into short wires of 2 cm in length, chemically polishing for 25 seconds with a mixed solution of phosphoric acid and ethanol in a volume ratio of 1:2, and then sterilizing by irradiation after vacuum packaging to obtain a coating-free biodegradable metal wire of 2 cm in length and 0.2 mm in diameter;
[0085] The heat sealing time of the vacuum package is 2.3 s, and the air extraction time of the vacuum package is 4.0 s.
[0086] The radiation sterilization uses a radiation source Co60, and the radiation sterilization time is 4 hours.
[0087] Performance Testing
[0088] Fifteen sheep aged 11 months and weighing 55 kg were randomly selected and randomly divided into three groups. The degradable metal fat-reducing threads prepared in Examples 1 and 2 and the uncoated degradable metal wires obtained in Comparative Example 1 were implanted in the fat layer of the tail of the sheep in each group, 20 wires were implanted in each sheep, and the corresponding implantation positions of different sheep were the same.
[0089] The percentage of the body weight of the sheep implanted with the degradable metal fat-reducing wires prepared in Examples 1 and 2 and the uncoated degradable metal wires prepared in Comparative Example 1 within 120 days was observed. Figure 2 As shown by Figure 2 It can be seen that the weight of the sheep with the uncoated degradable metal wire in Comparative Example 1 rebounded significantly 60 days after implantation, while the weight of the sheep with the coated degradable metal wire in Examples 1 and 2 did not rebound after implantation, and the fat reduction effect was more lasting.
[0090] Randomly select one sheep implanted with the degradable metal fat-reducing thread prepared in Example 2 and the uncoated degradable metal wire prepared in Comparative Example 1 on the 15th, 30th, 60th, 90th and 120th day, and prepare and detect the adipose tissue section staining images of the same implantation position of the sheep's tail on the 15th, 30th, 60th, 90th and 120th day as shown in the figure. Figure 3 As shown, further statistics and calculations were performed to obtain the change in the area of fat cells over time of the degradable metal wire prepared in Example 2 and the uncoated degradable metal wire prepared in Comparative Example 1 implanted in the sheep's tail within 120 days. Figure 4 As shown by Figure 3 and Figure 4 It can be seen that the fat cells in the tail of the sheep implanted with the degradable metal wire prepared in Example 2 gradually became smaller within 120 days, while the fat cells in the tail of the sheep implanted with the uncoated degradable metal wire prepared in Comparative Example 1 decreased within the first 60 days, but rebounded after the 60th day.
[0091] The weight loss rate of the degradable metal wire prepared in Example 2 and the uncoated degradable metal wire prepared in Comparative Example 1 implanted in the sheep's tail within 120 days is shown in the following figure: Figure 5 As shown, the uncoated metal wire in Comparative Example 1 was completely degraded 60 days after implantation in the sheep's tail, and could not play a long-term fat-reducing role; while the degradable metal wire with a polymer coating thickness of 10 μm prepared in Example 2 had not been completely degraded 120 days after implantation in the sheep's tail, which prolonged the fat consumption time and maintained the effective duration for a long time, thereby avoiding rebound and multiple thread embedding.
[0092] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A degradable metal fat-reducing thread, characterized in that: It comprises a degradable metal wire and a polymer coating covering the surface of the degradable metal wire; The polymer coating is composed of an absorbable polymer.
2. The degradable metal fat-reducing thread according to claim 1, characterized in that: The material of the degradable metal wire is magnesium, zinc or magnesium-zinc alloy, and the diameter of the degradable metal wire is 0.07-0.3 mm.
3. The degradable metal fat-reducing thread according to claim 1, characterized in that: The absorbable polymer is at least one of polylactic acid, poly-L-lactic acid PLLA, polylactic acid-glycolic acid copolymer PLGA, polydioxanone PDO, and poly-p-dioxanone PPDO.
4. The degradable metal fat-reducing thread according to claim 1 or 3, characterized in that: The thickness of the polymer coating is 2-30 μm.
5. A method for preparing the degradable metal fat-reducing thread according to any one of claims 1 to 4, characterized in that: The steps include: (1) hot extruding and hot drawing a degradable metal ingot in sequence to obtain a wire; (2) cutting and polishing the wire obtained in step (1) in sequence to obtain a polished wire; (3) spraying an absorbable polymer on the surface of the polished wire obtained in step (2) to form a polymer coating to obtain a degradable metal fat-reducing wire.
6. The preparation method according to claim 5, characterized in that: The extrusion ratio of the hot extrusion in the step (1) is (180-500):1, the extrusion temperature of the hot extrusion is 220-500°C, and the diameter of the hot extruded wire is 0.5-3 mm.
7. The preparation method according to claim 5, characterized in that: The hot drawing in step (1) is a multi-pass drawing, and the diameter of the wire material is reduced by 0.1 to 0.2 mm in each drawing pass. The temperature of the hot drawing is 70 to 120°C.
8. The preparation method according to claim 5, characterized in that: The length of the wire material after cutting in the step (2) is 1 to 4 cm.
9. The preparation method according to claim 5, characterized in that: The polishing liquid used in the step (2) is a mixture of phosphoric acid and ethanol, the polishing time is 15 to 40 seconds, and the polishing temperature is 10 to 35°C.
10. Use of the degradable metal fat-reducing thread according to any one of claims 1 to 4 in the preparation of a thread embedding device.